1992
DOI: 10.1111/j.1469-8749.1992.tb11386.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Post‐traumatic Amnesia in Young Children

Abstract: SUMMARY To assess the duration of post‐traumatic amnesia (PTA) in children, a new procedure is described, derived from a method described previously for adults. The procedure was tested on 70 healthy children between 3·5 and 10 years of age, then applied in a longitudinal prospective study of 54 children with brain damage resulting from closed head‐injury. The procedure consistently measured PTA in children of various ages. The duration of PTA was found to be as good a prognostic indicator for the occurrence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…These findings replicate the earlier work of Ruijs et al [21], who reported that TFC + PTA did not add value beyond TFC for examining short- and long-term outcomes after paediatric TBI. These results also support earlier work by Suskauer et al [2] demonstrating that TFC alone was a better predictor of functional outcome for children with TBI at both discharge from inpatient rehabilitation and 3-month follow-up.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These findings replicate the earlier work of Ruijs et al [21], who reported that TFC + PTA did not add value beyond TFC for examining short- and long-term outcomes after paediatric TBI. These results also support earlier work by Suskauer et al [2] demonstrating that TFC alone was a better predictor of functional outcome for children with TBI at both discharge from inpatient rehabilitation and 3-month follow-up.…”
Section: Discussionsupporting
confidence: 90%
“…Although TFC + PTA has been reported to be the best injury severity indicator for adult long-term follow-up [11, 12, 14, 15, 20], the paediatric literature has been less consistent [8, 18, 19]. Previous paediatric studies have found that TFC was a better predictor of WeeFIM® scores 3 months post-discharge [2] and that TFC demonstrated stronger correlations with outcome (GOS) than TFC + PTA at 3 months, 1 year and 2 years post-injury [21]. It was hypothesized that TFC would remain the best predictor of longer term functional outcome, as measured by WeeFIM® scores at 1 year post-discharge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Global outcome scales, including GOS and DRS, can be heavily influenced by cognitive function, and TFC+PTA has been shown to predict these outcomes [19,42,43]. TFC+PTA is also more predictive of cognitive outcome, as measured by neuropsychological testing [28].…”
Section: Discussionmentioning
confidence: 99%
“…TFC+PTA is predictive of global functional outcome, as measured by the GOS, at hospital discharge and at 3, 12, and 24 months post-injury [42, 43]. TFC+PTA has also been shown to predict performance on specific neurobehavioral measures at 3 weeks following normalization of COAT score and at 1 year post-injury [28].…”
Section: Introductionmentioning
confidence: 99%